Resisted sprint training in youth: the effectiveness of backward vs. forward sled towing on speed, jumping, and leg compliance measures in high-school athletes - Uthoff, A.; Oliver, J.; Cronin, J.; Winwood, P.; Harrison, C.; Lee, J. E. (The Journal of Strength and Conditioning Research, 2021)
Resisted sprinting (RS) is a popular training method used to enhance sprinting performance in youth. However, research has only explored the effects of forward RS (FRS) training. We examined the effects of FRS and backward RS (BRS) and compared these with a traditional physical education curriculum (CON). One hundred fifteen boys (age 13-15 years) were matched for maturity and allocated to either an FRS (n = 34), BRS (n = 46), or CON (n = 35) group. Training groups towed progressively overloaded sleds (20-55% body mass) 2 d·wk-1 for 8 weeks. Pre-training and post-training data were collected for sprinting times over 10 and 20 m, countermovement jump (CMJ) height, and leg stiffness (KN). Performance remained unchanged for the CON group (all p > 0.05), whereas all variables significantly improved (p < 0.05) after BRS, and all but 10-m performance improved after FRS. Compared with the CON, BRS and FRS significantly (p > 0.05) improved CMJ (Effect size [ES] = 0.67 and 0.38) and KN (ES = 0.94 and 0.69), respectively. No differences were found between training groups. The probabilities of improving sprinting performance after BRS (~70%) were on average ~10 and ~8% better than the FRS and CON groups, respectively. The BRS and FRS showed similar probabilities of improving CMJ (75 and 79%) and KN (80 and 81%), respectively, over the CON group. It seems that BRS may be a means to improve sprint performance, and regardless of direction, RS seems to be a beneficial method for improving jumping height and leg stiffness in youth male athletes.